2019
DOI: 10.1097/bpo.0000000000001017
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Patellar Instability: Implications of Preoperative Patellar Crepitation on the Status of the Patellofemoral Articular Cartilage

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Mankin's score was larger in the HS group versus the age-matched control group at Week 8 (5 [4.5-7.75] vs. 2.5 [1][2][3][4], p < 0.001), indicating that osteoarthritic changes occurred in the PF joint after 8 weeks of HS.…”
Section: Mankin's Scores Are Shown In Figurementioning
confidence: 93%
See 2 more Smart Citations
“…Mankin's score was larger in the HS group versus the age-matched control group at Week 8 (5 [4.5-7.75] vs. 2.5 [1][2][3][4], p < 0.001), indicating that osteoarthritic changes occurred in the PF joint after 8 weeks of HS.…”
Section: Mankin's Scores Are Shown In Figurementioning
confidence: 93%
“…Patellar instability frequently presents during adolescence, and patellofemoral (PF) symptoms (e.g., pain and instability) are the prelude to a lifelong condition 1 . Luhmann et al reported that PF joint damage was present in 63% of knees treated for patellar instability 2 . In animal models, experimentally induced patellar instability resulted in dysplastic changes in the femoral trochlea 3–6 and arthritic changes in the PF joint 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krepitation Krepitationsphänomene im femoropatellaren Gleitlager sind bei Patienten mit vorderem Knieschmerz häufig nachweisbar und können auf eine Chondropathie bzw. auf eine Synovialitis hindeuten [11,12].…”
Section: Sonstige Klinische Untersuchungenunclassified
“… 12 , 13 , 14 However, the incidence of articular cartilage disease after initial and recurrent patellar dislocation remains poorly understood, and there is a paucity of literature comparing the extent of cartilage damage between first-time and recurrent dislocations. 1 , 7 , 15 , 16 , 17 , 18 , 19 , 20 , 21 …”
mentioning
confidence: 99%